THE EFFECT OF MARINE SPONGE Aaptos aaptos EXTRACT IN VIBRIOSIS TREATMENT OF BLACK TIGER SHRIMP Penaeus monodon LARVAE - Rosmiati Rosmiati; Najiah Musa; Habsah Mohammad; Tengku Sifzizul Tengku Muhammad; Andi Parenrengi; Wahyuni Wahyuni (Indonesian Aquaculture Journal, 2014)
Black tiger shrimp Penaeus monodon post larvae were challenged with Vibrio harveyi and butanol extract of selected marine sponge Aaptos aaptos to determine its antibacterial bioactive potential in vibriosis treatment. Based on the preliminary toxicity study, the A. aaptos butanol extract with concentrations of 31.25, 62.5, and 125 mg/L were selected in the study. Black tiger shrimp post larvae were challenged with V. harveyi at 107 cfu/mL and immersed A. aaptos butanol extract with the concentration of 125 mg/L showed significantly in (P<0.05) decrease mortality of the post larvae treated. Besides at this concentration, V. harveyi population in the rearing water and the post larvae treated decreased compared to control (untreated post larvae). Histological observation indicated that there was no changing on hepatopancreas of the black tiger shrimp post larvae. Based on this result, it is suggested that the butanol extract of A. aaptos is a potential bioactive compounds source in the treatment of vibriosis which may replaced the current antibiotics application.